Chronic Dietary Administration of the Glycolytic Inhibitor 2-Deoxy-D-Glucose (2-DG) Inhibits the Growth of Implanted Ehrlich's Ascites Tumor in Mice. - Saurabh Singh; Sanjay Pandey; Anant Narayan Bhatt; Richa Chaudhary; Vikas Bhuria; Namita Kalra; Ravi Soni; Bal Gangadhar Roy; Daman Saluja; Bilikere S Dwarakanath (PLoS ONE, 2015)
Dietary energy restriction (DER) has been well established as a potent anticancer strategy. Non-adoption of restricted diet for an extended period has limited its practical implementation in humans with a compelling need to develop agents that mimic effects similar to DER, without reduction in actual dietary intake. Glycolytic inhibitor, 2-deoxy-D-glucose (2-DG), has recently been shown to possess potential as an energy restriction mimetic agent (ERMA). In the present study we evaluated the effect of dietary 2-DG administration on a mouse tumor model, with a focus on several potential mechanisms that may account for the inhibition of tumorigenesis.Swiss albino strain 'A' mice were administered with 0.2% and 0.4% w/v 2-DG in drinking water for 3 months prior to tumor implantation (Ehrlich's ascites carcinoma; EAC) and continued till the termination of the study with no adverse effects on general physiology and animal growth. Dietary 2-DG significantly reduced the tumor incidence, delayed the onset, and compromised the tumor growth along with enhanced survival. We observed reduced blood glucose and serum insulin levels along with decreased proliferating cell nuclear antigen (PCNA) and bromodeoxyuridine positive (BrdU+) tumor cells in 2-DG fed mice. Also, reduced levels of certain key players of metabolic pathways such as phosphatidylinositol 3-kinase (PI3K), phosphorylated-Akt and hypoxia inducible factor-1 alpha (HIF-1α) were also noted in tumors of 2-DG fed mice. Further, decrease in CD4+/CD8+ ratio and T-regulatory cells observed in 2-DG fed mice suggested enhanced antitumor immunity and T cell effector function.These results strongly suggest that dietary 2-DG administration in mice, at doses easily achievable in humans, suitably modulates several pleotrophic factors mimicking DER and inhibits tumorigenesis, emphasizing the use of ERMAs as a promising cancer preventive strategy.